ANALYSIS OF PHYSICO-MECHANICAL PROPERTIES OF KNITTED FABRIC WOVEN ON A JACQUART MACHINE - Jo'rabayev Abdurashid Toramirzayevich; Nuriddin Karimov Mahamadjonovich; Kenjayeva Vasila Kabulovna (Zeta Repository, 2023)
The article presents the analysis of the physical-mechanical indicatorts of the jacquard interlock knitted fabric sample taken on the 28 class “HANMA”machine, the type of weaving, the fiber content and the characteristics of moisture elasticity.